DEVELOPMENT OF ELECTRONIC TEACHING MATERIALS BASED ON SMART APPLICATION CREATOR (SAC) TO IMPROVE CONTEXTUAL THINKING ABILITY OF VIII JUNIOR HIGH SCHOOL STUDENTS ON VIBRATION AND WAVE MATERIALS - Ida Romatul Fitriah; Edi Irawan (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
The ability to think contextually has an important role in everyday life, with the ability to think contextually high will support the useful value of science in real life. However, in reality, many students are classified as lacking in contextual thinking skills. Because of this, the researchers compiled electronic teaching materials based on Smart Application Creator (SAC) which presented interesting and contextual teaching materials on Vibrations and Waves with the hope of improving students' contextual thinking skills. The method used by researchers is R&D through 4 stages, namely define, design, develop and disseminate. Data collection through questionnaires and tests, then carried out descriptive quantitative analysis. The final results of the study are: 1) the teaching materials prepared by the researcher are suitable for use both in terms of material (97.395%) and from the aspect of media assessment (100%). 2) The teaching materials that are arranged have a practicality level of 100% with a very practical conclusion to use. 3) Teaching materials prepared by researchers are effective in improving students' contextual thinking skills. Because there is an average difference between the pretest and posttest learning outcomes, the average posttest score is higher. 4) The teaching materials prepared by the researchers were very interesting (88.83%). So that overall it can be concluded that smart application creator (SAC) based electronic teaching materials are feasible to use.